The communication situation and the language of the original “Contemporary Music” series in Newonce Radio - Stachyra, Grażyna (Papers in Linguistics, 2023)
The article investigates the language of the original music programme “Contemporary Music” in the Newonce Radio internet station. The problem is addressed to revise the linguistic consequences of the change in the communication situation in the modern-day radio. Such a situation is understood here as a communication context that includes technological matters and the evolution of the original programming formula. This context is co-created by the following aspects: 1. Newonce Radio is not a separate institution – a radio station per se, but one of the channels of the Newonce.media platform; 2. It broadcasts one-time original music programmes which are later available as podcasts; 3. Original music programmes are hosted by the creators of audio industry (not music journalists) who invite industry friends as guests. Having those aspects in mind, the language of conversations between the presenters and the guests invited to the studio was examined. Hence, the theory of media linguistics was applied as regards the radio language variety, which made it possible to interpret the language of conversations in the pragmatic approach and proved that: 1. Broadcasting a programme that afterwards becomes a podcast leads to defining the communication space vaguely and distorting the way the language used is adapted to the mode of conversation on the radio “live” or performance in the recorded podcast; 2. Contesting the role of music journalists by the presenters influences the genre determinants of the programme: its intrinsic control character (the guests in the broad cast are friends of the hosts) and the status of the programme host (equal to the guests).